Senior High School Students’ Competence in the Use of Calculator in Mathematics Learning - Larbi, Ernest; Appiagyei , Ebenezer; Banson, Gideon Mensah (EDUPEDIA Publisher, 2024)
Scientific calculators serve as valuable tools for teaching and learning mathematics. Calculators help learners to understand mathematical concepts and computation. This study investigated students’ knowledge of the use of calculators in learning mathematics. The sample comprised 98 senior high school students, selected using a simple random technique. The quantitative study used a developed questionnaire with an internal consistency of 0.72 and a mathematics achievement test (MAT) to collect data. Mean and standard deviation, frequency, and Pearson product-moment correlation were used to analyse the data. The findings showed that the students have high hopes (above 3.72) about their ability to use calculators to solve problems in mathematics. The study also found that the student’s proficiency in using the calculator to solve the tasks involved was moderate. In addition, findings show that although there was a positive correlation between the students’ perceived competence and proficiency in calculator use, the correlation coefficient was weak (r = 0.341). Thus, the degree of their perceived capability did not match their actual calculator use. Teachers should continue to provide the needed support to enhance students’ understanding of the basic functions of the calculator and enhance their efficient use.